4 Bridges to transplant. (9th April 2018) - Hayward, Christopher S
Abstract : Heart transplantation remains the gold standard treatment for end-stage heart failure. By definition, these patients are unwell, and unfortunately a proportion will die waiting for transplant. The journey to transplantation is usually characterised by recurrent hospitalisations and may be complicated by progressive organ dysfunction. Optimisation of patient outcomes involves upward titration of evidence-based therapy (Ponikowski, et al. 2016), however, in this cohort treatment is often gradually withdrawn due to patient hypotension, renal dysfunction or other organ failure (Baumwol, 2017). Intermittent diuretic therapy has been suggested, with limited evidence of long-term benefit. Short-term mechanical support with intra-aortic balloon pumping or extra-corporeal membrane oxygenation allows stabilisation in cardiogenic shock, but is often of insufficient duration to bridge to successful transplantation without complication. Newer less invasive devices may be associated with fewer complications, but have not been shown to be more durable at this point. Chronic mechanical supports, as afforded by left ventricular assist or total artificial heart devices, offer a durable solution and have been shown to improve survival as well as symptoms in end-stage heart failure patients (Aaronson, et al . 2012; Starling, et al . 2011). The success of smaller continuous flow LVADs, especially, has increased the number of patients being supported on device waiting for heart transplantation and short-term outcomes approach that of heart transplantation (Mancini & Colombo, 2015). It is hoped that improvements in LVAD technology will further improve outcomes. References: . Aaronson K, et al. Use of an intrapericardial, continuous flow, centrifugal pump in patients awaiting heart transplantation. Circulation2012;125(25):3191–3200. . Baumwol J. 'I Need help'-A mnemonic to aid timely referral in advanced heart failure. J Heart Lung Transplant2017;36(5):593–594. . Mancini D, Colombo PC. Left ventricular assist devices: A rapidly evolving alternative to transplant. J Am Coll Cardiol2015;65(23):2542–2555. . Ponikowski P, Voors AA, et al. ESC guidelines for the diagnosis and treatment of acute and chronic heart failure: The task force for the diagnosis and treatment of acute and chronic heart failure of the European Society of Cardiology (ESC). Eur Heart J2016;37:2129–2200. . Starling RC, et al. Results of the post-U.S. food and drug administration-approval study with a continuous flow left ventricular assist device as a bridge to heart transplantation: A prospective study using the INTERMACS. J Am Coll Cardiol2011;57(19):1890–1898.